2018
DOI: 10.1371/journal.pone.0203825
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessed goal achievement (SAGA) after Holmium laser enucleation of the prostate (HoLEP): Association with patients' postoperative satisfaction

Abstract: This study aimed to determine serial changes in self-assessed goal achievement (SAGA) and treatment satisfaction after HoLEP, to identify correlations between the two, and to compare them with results assessed by traditional outcome measures. For a total of 170 patients, outcomes were evaluated serially at postoperative 1-, 3-, 6-, and 12-months using IPSS, OABSS, SAGA questionnaires and uroflowmetry. The SAGA questionnaire consisted of five questions including one open-ended question (self-assessed goals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Lee et al [26] reported that 91.8% of patients were satisfied with the surgical outcomes of HoLEP, and 94% reported that they would choose surgery if they had to reconsider. Our study showed improvements in objective and subjective symptoms in the 6-month analysis, which is consistent with recent studies [27].…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al [26] reported that 91.8% of patients were satisfied with the surgical outcomes of HoLEP, and 94% reported that they would choose surgery if they had to reconsider. Our study showed improvements in objective and subjective symptoms in the 6-month analysis, which is consistent with recent studies [27].…”
Section: Discussionsupporting
confidence: 93%
“…Further supporting the importance of communicating patient defined goals and expectations, 170 patients were examined across validated surveys before and after HoLEP at 1, 3, 6 and 12 months (13). Prior to HoLEP, patient determined key self-assessed goals of the treatment and were subsequently asked to provide self-assessed goal achievement (SAGA) and overall satisfaction scores.…”
Section: Discussionmentioning
confidence: 99%
“…Out of this cooperation, we were able to learn that standardised patient-reported outcome measures (ie, questionnaires) and voiding parameters often do not address the main concern of individual patients appropriately. Therefore, we included the SAGA 22 in the present trial. Thus, patients can define their main treatment goals prior to treatment, and achievement of goals according to a Likert scale is assessed at each study visit.…”
Section: Ethics and Disseminationmentioning
confidence: 99%